Climate and conflict: Untangling the evidence with a quantitative lens - Mastrorillo, Marina; Nina, von Uexkull; Jürgen, Scheffran (2025)
This podcast episode explores the technical backbone of climate–conflict research — the data, models, and analytical methods that help researchers understand how climate risks interact with insecurity, displacement, and conflict. Hosted by Marina Mastrorillo, Senior Economist at CGIAR, the conversation features two leading scholars: Prof. Nina von Uexkull (University of Konstanz / Uppsala University) and Prof. Jürgen Scheffran (University of Hamburg).